Tg(arcsin1/3+arccos1/4)

Tg(arcsin1/3+arccos1/4)
Гость
Ответ(ы) на вопрос:
Гость
Нужна формула : tg(α + β) = (tgα + tgβ)/(1 - tgα*tgβ) tg(arcSin1/3 + arcCos1/4) =  =(tg(arcSin1/3 ) + tg(arcCos1/4)) /(1 - tg(arcSin1/3 )*tg(arcCos1/4)) теперь по частям: tg(arcSin1/3 ) = 1/3 : √(1 -1/9) = 1/3 : √8/9= 1/3 : 2√2/3= 1/2√2 = √2/4 tg(arcCos1/4) = √(1 - 1/16) : 1/4 = √15/16:1/4 = √15 теперь наш пример: числитель = √2/4 + √15 = (√2 + 2√15)/4 знаменатель = 1 = √2/4 * √15 = 1 - √30/4 = (4 - √30)/4 итог:(√2 + 2√15)/4  :  (4 - √30)/4= (√2 + 2√15)/(4 - √30)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы